Tonalite-trondjemite-granodiorite formation of the Archaean. Special features of composition and conditions of formation, Ukrainian Shield as an example - О.В. Усенко (Геофизический журнал, 2021)
Tonalite-trondjemite-granodiorite formation (TTG) produces the main volume of acidic rocks of the continental crust. Similar rocks are never met later. Therefore the problems of their production are directly connected with the problem of the crust and mantle formation.